Internet and Distributed Computing Systems 6th International Conference, IDCS 2013, Hangzhou, China, October 28-30, 2013, Proceedings - Pathan, Mukaddim; Wei, Guiyi; Fortino, Giancarlo; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the 6th International Conference on Internet and Distributed Computing Systems, IDCS 2013, held in Hangzhou, China, in October 2013. The 20 revised full papers and 13 invited papers presented were carefully reviewed and selected from numerous submissions. The papers cover the following topics: ad-hoc and sensor networks, internet and Web technologies, network operations and management, information infrastructure; resilience, as well as fault tolerance and availability.
A Network-Controlled Approach for the Timely and Reliable Acquisition of Bursty Data in WMSNs -- Minimizing Nested Interrupts of Secondary Users in Multi-Priority Cognitive Radio Networks -- ContactSim: An Efficient Realistic Trace Driven Contact Simulator for Vehicular Opportunistic Networks -- A Stability-Aware Cooperative Routing Scheme in Multi-rate Mobile Ad-Hoc Wireless Networks -- Using Human-Centric Wireless Sensor Networks to Support Personal Security -- Toward Efficient Packet Buffering and Congestion Control Approaches for Reliable Data Delivery in Mobile Ad Hoc Network -- On Using Bittorrent for File Sharing in Mobile Ad-Hoc Networks -- Self-healing Schemes Suitable for Various WSNs -- RAS: A Task Scheduling Algorithm Based on Resource Attribute Selection in a Task Scheduling Framework -- A Model-Driven Service Integrated Framework Based on Three-Layer Ontology -- An Improved Collaborative Filtering Approach Based on User Ranking and Item Clustering -- Reporting an Experience on Design and Implementation of e-Health Systems on Azure Cloud -- Content Delivery Technologies: A View from ChinaCache -- Quality Control for Crowdsourcing with Spatial and Temporal Distribution -- A 2.4-GHz Fractional-N PLL Frequency Synthesizer with a Low Power Full-Modulus-Range Programmable Frequency Divider -- Multiple Sources Network Coding Signature in the Standard Model -- A Study of LDoS Flows Variations Based on Similarity Measurement -- Bit Reversal Broadcast Scheduling for Ad Hoc Systems -- Personal Health Records Integrity Verification Using Attribute Based Proxy Signature in Cloud Computing -- Dynamic Scheduling for Usable Service in Network Robot -- Relocation Matching for Multiple Teams in Electric Vehicle Sharing Systems -- A Task Scheduling Algorithm Considering Bandwidth Competition in Cloud Computing -- A Discovery Service for Smart Objects over an Agent-Based Middleware -- Research on an Adaptive Routing Mechanism of Combination of Packet Forward with Virtual Circuit -- Access-Load-Aware Dynamic Data Balancing for Cloud Storage Service -- Term-Based Approach for Semantic Similarity of Short Texts -- Two MRJs for Multi-way Theta-Join in MapReduce -- Dependability Modeling and Certification of Cloud-Based Distributed Systems -- Design of a Transmission-Aware Fault-Tolerant CAN Network -- Quantitative Model of Personnel Allocation Based on Information Entropy -- An Intelligent Complex Event Processing with D-S Evidence Theory in IT Centralized Monitoring -- Quantitative Dependability Assessment of Distributed Systems Subject to Variable Conditions.
Keywords: Computer science; Computer Communication Networks; Software engineering; Data protection; Computer software; Information storage and retrieval systems; Computer Science; Computer Communication Networks; Information Systems Applications (incl. Internet).; Algorithm Analysis and Problem Complexity; Systems and Data Security; Information Storage and Retrieval; Software Engineering